2008
DOI: 10.1371/journal.pone.0002238
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Nuclear Signalling of Estrogen Receptor to Breast Cancer Cytoskeletal Remodelling, Migration and Invasion

Abstract: BackgroundEstrogen is an established enhancer of breast cancer development, but less is known on its effect on local progression or metastasis. We studied the effect of estrogen receptor recruitment on actin cytoskeleton remodeling and breast cancer cell movement and invasion. Moreover, we characterized the signaling steps through which these actions are enacted.Methodology/Principal FindingsIn estrogen receptor (ER) positive T47-D breast cancer cells ER activation with 17β-estradiol induces rapid and dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
96
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 28 publications
9
96
1
3
Order By: Relevance
“…For instance, it may act through other transcription factors binding to their respective response elements (Dahlman-Wright et al, 2006). In addition, it has been demonstrated that extra-nuclear ER can activate protein kinases (Giretti et al, 2008;Migliaccio et al, 1996;Simoncini et al, 2000). Contrary to the results shown by Le May et al (2006) that exclusively found ER in -cell nuclei, our data indicate that in -cells, ER is located inside and outside the nucleus .…”
Section: E2 and Bpa Are Equally Effective Through A Non-classical Estcontrasting
confidence: 99%
“…For instance, it may act through other transcription factors binding to their respective response elements (Dahlman-Wright et al, 2006). In addition, it has been demonstrated that extra-nuclear ER can activate protein kinases (Giretti et al, 2008;Migliaccio et al, 1996;Simoncini et al, 2000). Contrary to the results shown by Le May et al (2006) that exclusively found ER in -cell nuclei, our data indicate that in -cells, ER is located inside and outside the nucleus .…”
Section: E2 and Bpa Are Equally Effective Through A Non-classical Estcontrasting
confidence: 99%
“…However, in addition to their role in canonical GPCR signalling, recent evidence suggests a more versatile role for Ga subunits. Studies from in vivo models have implicated Ga in mitotic spindle organisation (Wilkie and Kinch, 2005) and microtubule and cytoskeleton dynamics (Giretti et al, 2008). Ga proteins are also involved in the regulation of Hippo-YAP (Yu et al, 2012) signalling.…”
Section: Regulation Of the F-actin Cytoskeleton By Ga Proteinsmentioning
confidence: 99%
“…Recent work from different laboratories shows that ERs located outside the nucleus activate different signal transduction pathways with multiple effects, such as cell growth and survival (Kousteni et al, 2001), cell migration (Giretti et al, 2008), and vasorelaxation (Simoncini et al, 2000). How can ERs, which unlike growth factor receptors are soluble and lack intrinsic enzyme activity, exert these stimulatory effects?…”
Section: The Complex Network Of Extra Nuclear Interactions Of Steroidmentioning
confidence: 99%
“…Inside the nucleus, these receptors interact with hundreds of proteins that in different ways regulate ER transcriptional action (O'Malley, 2005). Outside the nucleus protein/protein interactions shape the signaling pathway followed by signal transduction from membrane to cell interior (Pawson, 2007).Recent work from different laboratories shows that ERs located outside the nucleus activate different signal transduction pathways with multiple effects, such as cell growth and survival (Kousteni et al, 2001), cell migration (Giretti et al, 2008), and vasorelaxation (Simoncini et al, 2000). How can ERs, which unlike growth factor receptors are soluble and lack intrinsic enzyme activity, exert these stimulatory effects?…”
mentioning
confidence: 99%